NURTURING SOCIAL SUPPORT: A CASE STUDY OF ADOLESCENT GIRLS IN BIRBHUM OVERCOMING SOCIAL BARRIERS - Madhura Sarkar (International Scientific and Current Research Conferences, 2023)
This case study explores the role of social support in helping adolescent girls overcome social barriers in the district of Birbhum. Adolescent girls often face multiple challenges such as gender inequality, limited access to education, early marriage, and restricted mobility. The study examines the social support system available to these girls and analyzes its impact on their well-being and empowerment. Through qualitative research methods, including interviews and focus group discussions, the study explores the types of social support received by adolescent girls, the sources of support, and the ways in which it helps them navigate social barriers. The findings highlight the significance of social support in enhancing the resilience and agency of adolescent girls, and provide insights for policymakers and practitioners to strengthen the social support system for adolescent girls in Birbhum.